RELATEDNESS BETWEEN K13 ENGLISH CURRICULUM AND WRITING MATERIALS IN BAHASA INGGRIS TEXTBOOK - Wirda Yanti; Alisa Franstia Maria Silaban; Erikson Saragih (English Language Teaching Prima Journal (ELT), 2021)
Abstract Textbook is an important media because contains learning materials that employed learners to get knowledge through learning process. To support the learning process, the textbook should be appropriate to the 2013 curriculum. This research used content analysis. The objectives of this research are (1) to explain the topics of writing materials in Bahasa Inggris textbook (2) to explain the writing materials written in Bahasa Inggris textbook (3) to explain the relatedness between writing materials and the K13 curriculum. Here, the result of this research shows that (1) The topic of writing material is appropriate to the 2013 curriculum. (2) The form of writing tasks meet as good criteria because the textbook gave good guideline and explanation exactly in social function, text structure and language feature. (3) The writing material in Bahasa Inggris textbook is related to the English 2013 curriculum because the writing material in the textbook have implemented based on the content of the syllabus of the 2013 curriculum. This textbook is good to use because it is suitable for students in Senior High School for the twelfth grade to increase their writing skills. Keywords : Content analysis, writing material, 2013 curriculum